2014
DOI: 10.1016/j.pbb.2013.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in response to amphetamine in adult Long–Evans rats performing a delay-discounting task

Abstract: The use of animal models to investigate experimental questions about impulsive behavior can provide valuable insight into problems that affect human health. The delay-discounting paradigm involves subjects choosing between smaller reinforcers delivered immediately and larger reinforcers that are delivered after a delay. This is an important experimental paradigm for examining impulsive choice in both laboratory species and humans. However, a shortcoming of previously published delay-discounting studies in anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 52 publications
6
38
0
1
Order By: Relevance
“…In delay discounting rats choose between a small/immediate reward and a large/delayed reward. Eubig et al (2014) investigated sex differences in delay discounting under the influence of amphetamine and found no baseline sex difference in delay discounting. However, drug treatment revealed a sex difference, with males selecting the large/delayed reward more than females when under the influence of amphetamine.…”
Section: Discussionmentioning
confidence: 99%
“…In delay discounting rats choose between a small/immediate reward and a large/delayed reward. Eubig et al (2014) investigated sex differences in delay discounting under the influence of amphetamine and found no baseline sex difference in delay discounting. However, drug treatment revealed a sex difference, with males selecting the large/delayed reward more than females when under the influence of amphetamine.…”
Section: Discussionmentioning
confidence: 99%
“…Within some of the rodent studies, however, there were more nuanced behavioral differences between males and females, suggesting that there may be subtle sex differences in intertemporal decision-making. For instance, Eubig et al (2014) reported that following acute administration of amphetamine, females were quicker to initiate trials and displayed more impulsive choices than males. In another study, males and females were characterized as “flat” or “steep” discounters based on their task performance; “steep” female discounters displayed a greater reduction in their preference for the large, delayed reward than their male counterparts at longer delays (Koot et al 2009).…”
Section: Sex Differences In Animal Models Of Decision-makingmentioning
confidence: 99%
“…These tasks provide rodents with a choice between a smaller, immediate reward or a larger delayed reward. Alterations in DA signaling alter this choice; however, the effects of amphetamine on impulsive choice are complex and vary with sex, strain, and paradigm . D 1 antagonists, as well as dopaminergic lesions to the dorsolateral striatum or the nucleus accumbens core, increase impulsive choice in delay‐discounting tasks in rodents, resulting in choice of the smaller nondelayed reward more often .…”
Section: Pathophysiologymentioning
confidence: 99%